Estudio retrospectivo de anomalías dentales y alteraciones óseas de maxilares en niños de cinco a catorce años de las clínicas de la facultad de odontología de la Universidad de Antioquia (2009)
ABSTRACT: The purpose of this study was to carry out an epidemiological retrospective study on the type and frequency of radiographic dental and bone alterations in patients from 5 to 14 years of age who consulted the Dental Clinic (Child and the Adolescent Clinics) of the College of Dentistry at the University of Antioquia between the years 2000 and 2002. Methods: 428 panoramic radiographs with adequate density, contrast and definition were analyzed using also the dental records as support. The films were read by a dental radiologist who defined the type of bone alterations and dental anomalies present. A descriptive statistical analysis was performed Results: the sample consisted of 232 males (54.20%) and 196 females (45.79%). In the Maxilla and Mandible: 33 x-rays were found with pathological radiolucent images (7.68%): 21 females (4.89%) and 12 males (2.79%); just one patient (0.23%) with pathological radio opaque images. In the teeth: 272 x-rays (63.40%) with presence of dental anomalies: 149 males (34.73%) and 123 females (28.67%), involving 1120 teeth. The anomalies found were: dens in dente, tooth agenesis, Taurodontism, macrodontia, conic shaped teeth, supernumerary teeth, microdontia, transpositions, fusions, mesiodens, retained teeth, gemination, enamel spur, and enamel pearls in this order of frequency. Conclusions: this study showed that the population affected with some radiographic abnormalities was 71.32%.